Analisis Flypaper Effect di Kabupaten/Kota Kalimantan Utara : Analisis Flypaper Effect di Kabupaten/Kota Kalimantan Utara - Yosua Serbujaya Sitompul (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
North Kalimantan, young province which inaugurated in 2012, has limited local revenues so it requires funds (Dana Perimbangan) from the central government. The funds should be a stimulus for regional self-reliance. However, In many ceses, the local government prefer to use balancing funds rather than explore their own potential, this behavior is known as the flypaper effect. This research was conducted to find the effect of Dana perimbngan and regional income on regional spending. In addition, this study aims to analyze whether there is a flypaper effect in the districts/cities in North Kalimantan using Panel Linear Regression Model. The result indicates no flypaper effect since not only Dana Perimbangan but also regional income significantly effect regional spending.